The Aspects of Solar and Geothermal Energy Conversion (Eurasian Research Bulletin, 2022)
In the article analyzed kinds various energy solar and geothermal energy sources and converters. The development of industry, technology and technology, the growth of energy resources, and environmental problems, determine the effect of energy capacity on the level of life conditions. The fact is that energy capacity is often the cause of the development and growth of growth technologies and more societal relations.